An Ideological Construction of the Indigenous Community: The Orang Asli as Portrayed in The Star Newspaper (KEMANUSIAAN The Asian Journal of Humanities, 2016)
Powerful western nations, especially those which control global news media, tend to portray less powerful nations through a Western-centric lens or perspective in globalised space. As such, less powerful nations are depicted as weak and powerless victims, reinforcing in the process prevailing power structures or unequal relations between powerful nations and less powerful ones. Minority groups are also not spared as they are, more often than not, depicted in a similar negative way. Interestingly, this is where the global connects with the local as mainstream media in the local front are inclined to construct minority groups such as the Orang Asli or indigenous community through the lens or perspective of the powerful elite. They are not given the space to speak for themselves and as such portrayed as weak and disempowered. The indigenous people are often marginalised by the mainstream media because they in part do not constitute a constituency considered politically important; neither are they regarded crucial by profit-oriented media because they do not have the purchasing power which advertisers relentlessly seek via the media. Given this scenario, this study examines the portrayal of the Orang Asli in a mainstream paper, The Star newspaper, from a critical discourse analysis perspective. Utilising van Dijk's Theory of Semantic Macrostructures and Theory of Ideology, the projection of the community is inspected through the analysis of macro elements that is thematic structure and micro elements comprising lexical, syntactic and rhetorical structures. Findings reveal that the "self" group members comprising the ruling or powerful elite and governmental organisations were positively depicted while the Orang Asli were portrayed in a negative and stereotypical fashion. Needless to say, media coverage of indigenous people globally has also often revolved around similar stereotypical images that are both pejorative and discriminatory.